2020
DOI: 10.26444/aaem/114913
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of <i>Mycobacterium</i> spp. in ornamental fish

Abstract: Introduction and objective. Fish mycobacteriosis is a chronic granulomatous disease caused by several species of bacteria from the genus Mycobacterium, described as nontuberculous mycobacteria (NTM). The most important species causing fish mycobacterioses are M. chelonae, M. fortuitum, and M. marinum. Mycobacteria infecting fish also include zoonotic pathogens. M. marinum is the cause of most cases of fish-related mycobacterial infection in humans. The disease occurs more frequently in workers in the fishing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Noteworthy, some of the currently identified bacteria are potentially zoonotic for humans. Many epidemiologic studies suggest that the water environment is the principal source of human exposure to NTM [ 24 , 32 , 33 ]. Reptiles and fish are often household pets, and if colonized, can be a source of pathogens for owners or other people exposed directly or indirectly to the animal via a contaminated environment [ 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, some of the currently identified bacteria are potentially zoonotic for humans. Many epidemiologic studies suggest that the water environment is the principal source of human exposure to NTM [ 24 , 32 , 33 ]. Reptiles and fish are often household pets, and if colonized, can be a source of pathogens for owners or other people exposed directly or indirectly to the animal via a contaminated environment [ 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiologic studies suggest that the water environment is the principal source of human exposure to NTM [ 24 , 32 , 33 ]. Reptiles and fish are often household pets, and if colonized, can be a source of pathogens for owners or other people exposed directly or indirectly to the animal via a contaminated environment [ 32 , 34 , 35 ]. Indeed, the incidence of mycobacterial diseases, particularly pulmonary mycobacteriosis, is growing in Europe and on other continents [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the lesions in kidney and spleen of goldfish were clearly suggestive of systemic mycobacteriosis. Mycobacteriosis is a common bacterial disease affecting ornamental fish (Noga, 2010;Delghandi et al, 2020;Puk and Guz, 2020), and goldfish is reported to be more prone to mycobacteriosis (Francis-Floyd, 2011). Importantly, systemic granuloma formation is the characteristic histopathological alteration of chronic mycobacterial infection in fish (Talaat et al, 1998;Martınez-Lara et al, 2021) and several non-tuberculous mycobacteria, namely M. marinum, M. fortuitum, M. chelonae and M. gordonae have been incriminated as etiological agent of mycobacteriosis in goldfish (Pate et al, 2005).…”
Section: O N L I N E C O P ÿmentioning
confidence: 99%
“…Astronotus ocellatus , Carassius auratus , Colisa lalia , Cyprinus carpio subsp. haematopterus , Danio rerio , Helostoma temminckii , Hyphessobrycon serape , Labidochromis caeruleus , Microgeophagus ramirezi , Paracheirodon innesi , Poecilia reticulata , Symphysodon discus , Trichogaster lalius , Xiphophorus helleri and X. maculatus ) ( 15 , 19 , 23 , 31 , 44 , 45 ). The most common NTM pathogens of fish include M .…”
Section: Introductionmentioning
confidence: 99%
“…marinum , M. fortuitum , M. peregrinum and M. chelonae . Other species isolated from fish include M. abscessus , M. arupense , M. avium , M. chesapeaki , M. conceptionense , M. flavescens , M. gordonae , M. haemophilum , M. kansasii , M. montefiorense , M. mucogenicum , M. neoaurum , M. nonchromogenicum , M. parascrofulaceum , M. porcinum , M. pseudoshottsii , M. salmoniphilum , M. saopaulense , M. scrofulaceum , M. senegalense , M. septicum , M. shimoidei , M. shottsii , M. simiae , M. terrae , M. szulgai , M. triviale , M. triplex , M. ulcerans and M. xenopi ( 18 , 23 , 34 , 41 , 43 , 44 , 45 ). In recent years, human nontuberculous mycobacterial infections and diseases have significantly increased ( 32 ).…”
Section: Introductionmentioning
confidence: 99%